The Role Of Visum Et Repertum In Domestic Violence Cases: A Case Study Of Decision Number 310/Pid.Sus/2025/Pn Ckr - Eliagita, Choralisa; Eryke, Herlita (Dinasti Research, 2026)
Domestic violence in Indonesia poses serious evidentiary challenges due to minimal independent witnesses and its occurrence within private family spaces. Visum et Repertum (VeR), as a medico-legal document, plays a strategic role in the criminal evidence system by providing objective proof of physical violence. This study analyzes VeR’s role in proving domestic violence cases, identifies implementation obstacles, and examines judicial considerations based on Decision Number 310/Pid.Sus/2025/PN Ckr. A normative juridical approach with case study method was employed, analyzing secondary legal materials through prescriptive-analytical qualitative analysis. The findings reveal that VeR performs essential functions in objectively documenting injuries, connecting wound characteristics with instruments of violence, strengthening victim testimonies, and serving as a primary judicial consideration in establishing the elements of Article 44 paragraph (1) of the Domestic Violence Elimination Law. In this case, VeR formed a coherent evidentiary construction with witness testimonies and physical evidence, resulting in an eight-month imprisonment sentence for the perpetrator.